2023
DOI: 10.1021/acs.analchem.3c02129
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Raman Spectrophotometer for Examining Drug-Induced and Chemical-Induced Cellular Changes in 3D Cell Spheroids

Hao-Xiang Liao,
Kazuki Bando,
Menglu Li
et al.

Abstract: Cell spheroids offer alternative in vitro cell models to monolayer cultured cells because they express complexities similar to those of in vivo tissues, such as cellular responses to drugs and chemicals. Raman spectroscopy emerged as a powerful analytical tool for detecting chemical changes in living cells because it nondestructively provides vibrational information regarding a target. Although multiple iterations are required in drug screening to determine drugs to treat cell spheroids and assess the inter-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…An adaptation of the multiwell RS system was used in 2023 to examine drug-induced cellular changes in 3D cell spheroids. 154 They investigated biochemical changes of HeLa and HepG2 spheroids subjected to Actinomycin D (ActD) and free fatty acid (FFA) treatments, respectively. In ActD-treated HeLa spheroids, Raman spectra revealed dose-dependent changes with a significant increase in the Raman intensity at 1485 cm −1 , and a decrease in the Raman intensity at 1585 cm −1 was observed with ActD treatment at a concentration range of 0.3−10 μM (Figure 5c.i−iii).…”
Section: ■ Imaging Drug Response Through Biochemical and Metabolic Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…An adaptation of the multiwell RS system was used in 2023 to examine drug-induced cellular changes in 3D cell spheroids. 154 They investigated biochemical changes of HeLa and HepG2 spheroids subjected to Actinomycin D (ActD) and free fatty acid (FFA) treatments, respectively. In ActD-treated HeLa spheroids, Raman spectra revealed dose-dependent changes with a significant increase in the Raman intensity at 1485 cm −1 , and a decrease in the Raman intensity at 1585 cm −1 was observed with ActD treatment at a concentration range of 0.3−10 μM (Figure 5c.i−iii).…”
Section: ■ Imaging Drug Response Through Biochemical and Metabolic Ch...mentioning
confidence: 99%
“…The authors applied this system to study drug polymorphism and alkyne-tag screening, and also demonstrated the capability for mapping relatively large samples. An adaptation of the multiwell RS system was used in 2023 to examine drug-induced cellular changes in 3D cell spheroids . They investigated biochemical changes of HeLa and HepG2 spheroids subjected to Actinomycin D (ActD) and free fatty acid (FFA) treatments, respectively.…”
Section: Imaging Drug Response Through Biochemical and Metabolic Changesmentioning
confidence: 99%